Legal Review of Unregistered Marriages Relating to Transfer of Rights to Property Obtained During Marriage for the Chinese Group - Taufik Hidayat Lubis; Hepy Krisman Laia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
According to Article 2 paragraph (1) of Law Number 1 of 1974 concerning Marriage, a marriage is considered valid if it is conducted according to the laws of the respective religion and beliefs. Marriage is not merely a physical union but also an emotional bond, and fundamentally follows the principle of monogamy. In the legal framework of marriage, state protection—particularly for wives and future children—can only be guaranteed if the marriage is consciously conducted in accordance with Law Number 1 of 1974, which includes the requirement that the marriage be officially registered under applicable laws and regulations.If a marriage is not registered, the state cannot provide legal protection concerning marital status, joint property, inheritance, and other rights arising from the marriage. To establish a wife’s rights, it must first be proven that a legal marriage exists between her and her husband. One legal consequence of an unregistered marriage is that neither the wife nor any children from the marriage have the right to claim support or inheritance from the husband. Islamic inheritance laws allocate shares specifically to blood relatives.Unregistered marriages—often called sirri, kiyai, or syar’i marriages—are conducted according to religious rules or customs but are not registered with the Marriage Registrar. In Chinese customary law, property acquired during marriage is influenced by a patrilineal kinship system, where the wife’s status is governed by the husband’s family law. Generally, the husband, as head of the household, controls all marital property and has absolute rights to use it without needing the wife’s consent, including in transferring joint property.